Kommunikációs elvárások a szervezetben - Juhász, Csilla (Közép-Európai Közlemények, 2016)
In my essay my aim was to show my expectancy model about expectancy pressure. There are in the organization some expectancy of managers, some expectancy of employees. Expectancies of organizations and managers are much more stronger, sophisticated than employee’s expectancy. Expectancy pressure comes from the measurement of power and size of different expectancies. Useful know that expectancy is a procedure and the success is not just depend on the way of motivation, but there is one basic thing, which really support or deny the result of this process. This one thing is the communication.In our empiric research my aim was to examine the expectancy for organizational communication. Managers filled a questionnaire. On the questioners we asked about expectancy of oral and written communication forms. The solution shows that the most important written communicational tool is the clear message and the most important oral communicational tool is the good communicative competence. The least of all important written communicational tool is compactness, and the least of all important oral communicational tool is empathy.My essay presents some problem of organizational communication. These are the followings: functional illiteration, communicational differences of genders, differing generations, communicational differences in differing generations, problems in active listening.